2016
DOI: 10.1093/mnras/stw206
|View full text |Cite
|
Sign up to set email alerts
|

Fast spinning strange stars: possible ways to constrain interacting quark matter parameters

Abstract: For a set of equation of state (EoS) models involving interacting strange quark matter, characterized by an effective bag constant (B eff ) and a perturbative QCD corrections term (a 4 ), we construct fully general relativistic equilibrium sequences of rapidly spinning strange stars for the first time. Computation of such sequences is important to study millisecond pulsars and other fast spinning compact stars. Our EoS models can support a gravitational mass (M G ) and a spin frequency (ν) at least up to ≈ 3.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 101 publications
(121 reference statements)
1
46
0
Order By: Relevance
“…The underlying model assumed in the simulations is the variational AP3 nucleonic EoS (red) [306]. The EoS models indicated in the figure are nucleonic (models AP3 and AP4) [306], but also schemes where the constituent species are quarks (u,d,s quarks) [361,362], nucleons and hyperons (inner core of hyperons, outer core of nucleonic matter) [363], or quarks and nucleons forming hybrid stars (inner core of uds quarks, outer core of nucleonic matter) [364]. The label CEFT indicates the range of a nucleonic EoS based on χEFT [365], whereas the pQCD is the range of nucleonic EoS that results from interpolating from CEFT at low densities and matching to perturbative QCD (pQCD) calculations at higher densities [366].…”
Section: Observational Constraintsmentioning
confidence: 99%
“…The underlying model assumed in the simulations is the variational AP3 nucleonic EoS (red) [306]. The EoS models indicated in the figure are nucleonic (models AP3 and AP4) [306], but also schemes where the constituent species are quarks (u,d,s quarks) [361,362], nucleons and hyperons (inner core of hyperons, outer core of nucleonic matter) [363], or quarks and nucleons forming hybrid stars (inner core of uds quarks, outer core of nucleonic matter) [364]. The label CEFT indicates the range of a nucleonic EoS based on χEFT [365], whereas the pQCD is the range of nucleonic EoS that results from interpolating from CEFT at low densities and matching to perturbative QCD (pQCD) calculations at higher densities [366].…”
Section: Observational Constraintsmentioning
confidence: 99%
“…Note that previous authors explored the stable structure of compact stars, which provided general information about the fast spinning compact star parameters (e.g., Cook et al , 1994). Some authors went a step further, considered the measured spin rate of an ms pulsar, and computed a constant spin sequence for that pulsar (e.g., Datta et al , 1998;Bhattacharyya et al , 2016). But such a sequence gives large ranges of other parameter values for a given EoS model.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the thermal emission comes from the whole surface, we could set the smallest radius of the SSs at 4km in this work. The corresponding masses and moment of inertias are obtained by employing EoS named pMIT (Bhattacharyya et al 2016), CDDM1 and CDDM2 (Li et al 2016), which are shown in Table 2. For comparison, the mass of SSs are set as 0.03164M ⊙ , 0.02234M ⊙ , 0.01829M ⊙ , respectively (which is calculated from EoSs with R = 4km),…”
Section: Eos and Pulsar Death Linementioning
confidence: 99%
“…The radius and moment of inertia for the specific mass of SSs with EoSs named pMIT, CDDM1 and CDDM2. The EoS named pMIT are recovered from Bhattacharyya et al (2016), EoSs named CDDM1 and CDDM2 are get from Li et al (2016). The smallest mass is got with the best fit small radius of CCO.…”
Section: Eos and Pulsar Death Linementioning
confidence: 99%